Fire Capsule / Wan Muhammad Syahmi Mohamad Nazir … [et al.] - Mohamad Nazir, Wan Muhammad Syahmi; Raja Zahudeen, Raja Yasmin Syahila; Amri, Nurul Aisya; Haripen, Siti Nur Athira; Roslan, Nurul Syafikah; Norhisham, Norshiba (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
Fire is one of the most important elements in surviving in the wilderness. It does not just provide a source of light, but it also benefits heat for keeping the wild animals away from your campsite, boiling contaminated water to keep you hydrated, cooking your delicious foods, and heating you to prevent hypothermia. Although many know that this element is essential in prolonging one’s survival needs, things may get out of hand even for outdoor enthusiasts such as experienced bush crafter, hikers, campers, expert people too cannot get away from being careless. Unexpected events like climate change, natural disasters, or even getting lost in the woods could be life threatening situations. Without proper training or the right supervision, starting a fire could be troublesome for certain people. Many ways can be learned in order to start a fire up, but why bother if you can be survival prepared by having an item that can be used for many purposes. The product that we are innovating is the so-called Fire Capsule. This product innovation came or inspired through observation, ideas and experiences gained by our own teammates during practices in the field. Fire Capsule aims to provide effective and efficient assistance to ensure compliance to the user. The main purpose of this product is to make the fire capsule easier to bring and use. This will help the targeted users such as outdoor activities users to use it easily anytime and anywhere.